Reassessing the anatomy and affinities of Mirischia asymmetrica (Theropoda: Coelurosauria) from the Early Cretaceous of Brazil - Delcourt, Rafael (2025)
Mirischia asymmetrica is known from a partially articulated specimen (SMNK 2349) from the Albian (Lower Cretaceous) Romualdo Formation of the Araripe Basin, Brazil. Often classified within Compsognathidae (Theropoda, Coelurosauria), its taxonomic affinity remains debated. We conducted a comprehensive anatomical reassessment of SMNK 2349, including new observations on its osteology and exceptionally preserved soft tissues. The axialskeleton exhibits a complex set of laminae, forming deep spinopostzygapophyseal fossae, dorsoventrally concave lateral surfaces of thefan-shaped neural spines, and a subdividedpostspinal fossa. The neural arches arecraniocaudally abbreviated and asymmetrically developed across the series. The pelvic girdle aswell as the hindlimb are particularly distinctive amongst coelurosaurs, preserving internal softtissues interpreted as remnants of the rectum.The intestinal tract is located near the pubic bootand exhibits a curved morphology like that seen in Scipionyx. Unlike the latter, the wide loopmade by the distalmost portion of the rectum is,however, preserved ventral to the ischium. The globular surface texture of the rectum ventral tothe right ischium is here interpreted as theimprint of the epidermal scales from theoverlying scaly skin. If true, this would indicate that the pelvic region of Mirischia was covered with minute pebbly tuberculate and larger irregular, often polarized basement scales instead of protofeathers such as filamentous, branched, or pennaceous integuments. Thefemora are bowed cranially with distinct proximal trochanters. The tibia offers anotherrare trait: the medial condyle of its proximal endbears a projected, spine-like caudal process.Although caudal projections of the tibial condyles occur sporadically in maniraptorans and tyrannosauroids, the prominence, and orientation of the caudal process of Mirischia is exceptional and appears to be restricted to some Gondwanan theropods such as Santanaraptor, Gualicho, and Deltadromeus. A rev ised phylogenetic analysis incorporating new morphological characters recovers Mirischia asan early-branching ornithomimosaurs. Therevised anatomical and phylogenetic evidencesuggests that Mirischia belongs to a still poorly documented lineage of Gondwanan coelurosaurs, highlighting the significant gaps in our knowledge on the relationships of basal coelurosaurs.